Modeling of tunneling current density of GeC based double barrier multiple quantum well resonant tunneling diode. (October 2018) - Dey, Swagata; Chakraborty, Vedatrayee; Mukhopadhyay, Bratati; Sen, Gopa
Abstract: The double barrier quantum well (DBQW) resonant tunneling diode (RTD) structure made of SiGeSn/GeC/SiGeSn alloys grown on Ge substrate is analyzed. The tensile strained Ge1− z C z on Si1− x − y Ge x Sn y heterostructure provides a direct band gap type I configuration. The transmission coefficient and tunneling current density have been calculated considering single and multiple quantum wells. A comparative study of tunnelling current of the proposed structure is done with the existing RTD structure based on GeSn/SiGeSn DBH. A higher value of the current density for the proposed structure has been obtained.